The changing shape of nursing practice : the role of nurses in the hospital division of labour - Allen, Davina, 1963- (Routledge, 2001)
"Bringing sociological theories and nursing practice together, The Changing Shape of Nursing Practice develops a conceptualisation of the nursing role which is rooted in the work seeting. It looks back to the factors which have shaped nursing work in the past and forward to those which are likely to shape it in the future." "Nurses' work is changing in two respects: in terms of the place nursing occupies within the health care division of labor and in terms of the routine shifting of work boundaries that nurses experience in their daily work. Davina Allen draws on her observations of the reality of nursing work in a district general hospital to explore these linked themes, focusing on five key work boundaries: nurse/doctor, nurse/manager, nurse/support worker, nurse/patient, and nurse/nurse." "The Changing Shape of Nursing Practice provides insight into many of the tensions and dilemmas nurses routinely face and the processes and constraints through which their work is fashioned."--Jacket